Education Financial Management in Senior High School: Manajemen Keuangan Pendidikan SMA - Muhammad Mu'ad Sahlan; Hidayatulloh Hidayatulloh (Academia Open, 2022)
The research method used is qualitative by using a descriptive approach to describe the phenomena that occur in this institution. SMA Muhammadiyah 1 Taman was made the object of research because it has implemented financial management well, marked by the rapid fulfillment of learning facilities and the dynamics of ongoing school activities. From the results of the study, it is known that: 1) the management of educational financial management, SMA Muhammadiyah 1 Taman has utilized information technology, utilized bank service products, and financial management software. the implementation of financial management is in accordance with the stages, starting from: a) planning for preparing activities, planning budgets, and determining sources of financial revenues; b) the organization includes the school principal, treasurer, reception treasurer staff, expenditure treasurer staff, BOS treasurer, BPOPP treasurer, wakasek as the executor of the activity; c) the implementation of activities has been carried out in accordance with the program of activities that have been planned, while the realization of the budget against the budget planning is carried out less than 100% due to arrears in tuition fees and student activity funds that have not been paid 100% by the parents of students; d) financial management control is carried out by i) Principals to school treasurers and budget users, ii) Government to principals regarding the use of BOS and BPOPP funds, iii) Persyarikatan Muhammadiyah to Principals regarding supervision and guidance on financial management sourced from parents students, and; e) accountability for budget use is carried out by i) treasurer and activity implementers to school principals, ii) school principals to the government related to the use of BOS and BPOPP funds, and school principals to Muhammadiyah organizations related to funds sourced from students' parents. Education Financial Management